The production of Spanish fiction series for SVOD: evolution, trends and strategies (Communication & Society, 2024)
The consolidation of digital television via subscription video on demand (SVOD) services has created an unprecedented increase in the consumption of serialised TV shows, which has had direct consequences on the content production sector. Faced with an increasingly demanding, hyperconnected and discerning audience and a supply of content never previously seen, television production and distribution strategies are involved in a process of change and adaptation. This paper seeks to analyse the production of Spanish television series created to be distributed on SVOD platforms. The aim is to know the role that production companies play in the creation of television series for SVOD so as to identify strategies and cooperative alliances between production companies and platforms and to detect possible patterns and trends in the operations of the audiovisual market. Using a mixed methodology that combines quantitative study with qualitative data analysis, the 88 Spanish TV series and miniseries that premiered on SVOD platforms from 2016 to 2021 are analysed, taking as a starting point the year in which these platforms began operating in Spain. The results confirm a trend towards cooperation between independent production companies and the platforms themselves, while no presence of in-house production is observed. Likewise, the atomisation of the role of production companies in the context of SVOD is shown, a phenomenon that already existed in generalist television production.